Executive Incentives，Technology Innovation and Corporate Performance ——Based on high-tech enterprise - Chen, Siyu (2019)
The 21 Century is the age of intelligent economy, scientific and technological innovation. At the same time, it is also an essential way for enterprises to continuously improve their competitiveness and achieve sustainable development. The ability of technological innovation has become the dominant factor in market competition. Under the modern enterprise system, executive incentives have the decision-making power and become the main force to promote technological innovation. As a key factor for enterprises to maintain their core competitiveness, technological innovation also plays a vital role in business performance. Through technological innovation, enterprises can adapt to social development and expand market share. R&D activities are characterized by large investment, high risk and long cycle, which are highly uncertain compared with the general investment activities of enterprises. This paper does the empirical research on Chinese GEM high-tech enterprises, through the combing of the existing research literature, establishing research hypotheses and models, using executive shareholding ratio and salary incentives as the perspective of analysing executive incentives. And then uses regression analysis methods to do empirical study. On the basis of the relationship between management incentives, technological innovation and corporate performance. Further exploration of whether technological innovation has an intermediary conduction effect between executive incentives and firm performance. Empirical studies have found that in GEM enterprises, the implementation of executive incentives can actively promote the improvement of business performance, and executive incentives can promote technological innovation.Technological innovation has some adjustment effects on executive incentives and corporate performance. Finally, this paper combines the research conclusions with the implementation of executive incentives and problems in the process of technological innovation.